A Critical Examination of Political Science Curriculum Implementation in Colleges of Education in Osun-State, Nigeria - Oderinde, Segun Lakin; Obadiora, Joseph Adebayo (Indonesian Journal of Education and Social Sciences, 2024)
The implementation of the political science curriculum in colleges of education is of utmost importance to ensure quality education and the development of informed and responsible citizens. This study examined the implementation of political science curriculum in colleges of education, Osun State. The paper examined the appropriateness of teaching strategies adopted by political science lecturers, the relevance of instructional materials used, and students’ attitudes towards the subject matter. A survey research design was adopted for the study. All political science students in colleges of education constituted the population of the study. A sample size of 500 respondents was involved in the study. Five colleges of education were selected for the study using the purposive sampling technique. Fifty political science students were selected from each of the five colleges of education using a simple random sampling technique. A questionnaire was used for data collection. The collected data was analysed using simple percentage. Findings revealed that political science lecturers in colleges of education employed appropriate teaching strategies. Findings also showed that political science lecturers made use of relevant materials in their teaching profession. The study found that most students showed a positive attitude towards learning political science, as evidenced by their regular attendance in the classes. Thus, the study came to the conclusion that the implementation of political science curriculum in colleges of education in Osun State, Nigeria, is effective.